1999
DOI: 10.1016/s0031-9422(99)00128-4
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor sterols from the mycelia of Cordyceps sinensis

Abstract: Activity guided fractionations led to the isolation of two antitumor compounds 5a,8a-epidioxy-24(R )-methylcholesta-6,22-dien-3b-D-glucopyranoside and 5,6-epoxy-24(R )-methylcholesta-7,22-dien-3b-ol from the methanol extract of Cordyceps sinensis. Two previously known compounds, ergosteryl-3-O-b-D-glucopyranoside and 22-dihydroergosteryl-3-O-b-D-glucopyranoside were also isolated. The structures of hitherto unknown sterols were established by 1D and 2D NMR spectroscopic techniques with the former synthesized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
173
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(186 citation statements)
references
References 26 publications
(26 reference statements)
7
173
0
2
Order By: Relevance
“…6B, 2005 column chromatography and identified as ergosterol and ergosterol 5α,8α-peroxide respectively, by comparison of their 1 H and 13 C NMR spectra with those reported in the literature. 7,8 The neocyclocitrinols (3) were obtained from the methanol phase. The hydroxyanthraquinones we reported before in another cultivation of the fungus, 5 were also obtained from this methanol phase.…”
Section: Resultsmentioning
confidence: 99%
“…6B, 2005 column chromatography and identified as ergosterol and ergosterol 5α,8α-peroxide respectively, by comparison of their 1 H and 13 C NMR spectra with those reported in the literature. 7,8 The neocyclocitrinols (3) were obtained from the methanol phase. The hydroxyanthraquinones we reported before in another cultivation of the fungus, 5 were also obtained from this methanol phase.…”
Section: Resultsmentioning
confidence: 99%
“…An extract was obtained from P. ostreatus which suppressed proliferation of breast cancer (MCF-7, MDA-MB-231) and colon cancer (HT-29, HCT-116) cells, without affecting proliferation of epithelial mammary MCF-10A and normal colon FHC cells [125]. Flow cytometry revealed that the inhibition of cell proliferation by P. ostreatus was associated with the cell cycle arrest at G0/G1 phase in MCF-7 and HT-29 cells.…”
Section: Other Immunotherapy Substances From Pleurotus Speciesmentioning
confidence: 99%
“…It was also recorded that a polysaccharide fraction from an ethanol-precipitable aqueous extraction of that fungus inhibited the proliferation and differentiation of the human leukemic U937 cells (55). Further studies on this species resulted in the isolation of bioactive sterols, which exhibited anti-tumor activities against various tumor cell lines such as the K562, Jurkat (T-lymphoblastic), HL-60 (promyelocytic leukemia), WM1341 (malignant melanoma) and RPMI (multiple myeloma) (56). An ethanolic extract from this fungus as well as cordycepin, a newly-discovered bioactive compound, were reported to possess anti-oxidant and anti-tumor activities such as inhibiting cell proliferation, and inducing apoptosis in colorectal and hepatocellular cancer (57).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%